English verb functions : an analytical study based on samples from short stories and academic articles - Siti Afifah Hashim (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2003)
This study identifies the verb functions in two genres, namely short stories and academic articles. A comparison is made between the two sets of texts to see whether there is any differnce in the use of verbs. The purpose behind the selection of these two genres is because these two genres are seen to differ from each other on its rhetorical organization. The study on English verb functions is done using the meaning-based framework as proposed by Reid (1991). In this framework, language is seen as a tool of communication that can be perceived and learnt as a system. The findings of this study show that verb can be categorized according to their functions. The verb functions identified include 'Temporal Relevance', 'Linguistic Factuality', 'Person', 'Verb Number' and 'Degree of Control'. The various forms appear to have their own distinctive features and help in conveying specific communicative messages. Apart from that, the sutdy also shows that there exists some differences concerning the verbs sed in both genres. It appears that both genres have their own patterns of verb use. For example, one feature is that short stories use more past forms that non-past form. Another is that, there is a greater use of the First and Second Person pronoun is short stories compared to academic articles. This may be due to the fact that short stories involve a lot of conversations and therrefore, there is a need for the deployment of the First and Second Person pronoun. In contrast, academic articles use more non-past forms that the past form. There are some similarities too in that there is widespread use of linguistically factual events in both short stories and academic articles. This shows that the events in both genres convey more more completed actions and thus, indicate linguistically 'true' messages. The study on verebs concerning the Degree of control tells that both genres have deployed the "Active form more than the Passive form. Clearly, it dawns on us that both genres allow the Actors/Agents greater control over the event. In terms of te Verb Number, it was found the both genres have verb patterns that flaunt the Subject-Verb Agreement Rule (SVA). When examined closely such instances reveal that they have been so constructed to convey a differing set of messages. A greater need to getting a precise message well conveyed has sosmehow led to the 'violation' of the SVA rule. The rule has been useful in detailing patterns of use that have been glossed over in grammar textbooks.